Penerbangan Perintis dalam Mengembangkan Perekonomian di Pulau Karimunjawa - Ryan Firdiansyah Suryawan; M. Fatchoelqorib (Institut Transportasi dan Logistik Trisakti, 2018)
This study aimed at analyzing the role of pioneer aviation in developing the economy of Karimunjawa Island. Survey was used as the research method. The population was taken from the community living in Karimunjawa Island, Jepara, Central Java and used 35 citizens as total sampling. The result shows that there is a significant role of pioneer aviation in connecting the economy of Karimunjawa Island. The score of t-count of variable X (pioneer aviation) affects the economy of the outer island (variable Y). The score of R-square is 0.661 which means the role of pioneer aviation has 66.1 % of the outer island while 33.9 % affects the factors that are not examined such as service, ticket price, aircraft capability, society income ability, airport facility, and others. Penerbangan Perintis dalam Mengembangkan Perekonomian di Pulau Karimunjawa